Prevalence and spectrum of congenital heart diseases in children - Khurshid Ahmed Wanni; Naveed Shahzad; Mohd Ashraf; Kaisar Ahmed; Muzafer Jan; Shafaqat Rasool (Heart India, 2014)
Background: Congenital heart disease (CHD) is one of the major causes of mortality and morbidity in the pediatric population of both the developing and developed countries. Variability in incidence and prevalence of CHD from various countries of Indian subcontinent and rest of the world could be because of genetic, cultural, and environmental factors. Objective: To find the prevalence and pattern of CHD in a tertiary care hospital in Kashmir (J&K). Materials and Methods: A retrospective analysis of case-records data of 767,921 patients (0-18 years) over 3 years and 10 months period was conducted to ascertain the prevalence and spectrum of CHDs. Results: A total of 877 patients out of 767,921, were found having CHDs measuring a prevalence of 1.12/1000. About 777 (88.5%) were the acyanotics, and 100 (11.5%) were cyanotic heart patients. Among the acyanotic heart diseases ventricular septal defect was the most frequent lesion seen in 241 (31.2%), followed by patent ductus arteriosus in 184 (24.3%) children. Among the cyanotic heart diseases tetralogy of Fallot was the most frequent cyanotic heart disease seen in 48 (48.0%) patients. Conclusion: Prevalence of 1.12/1000 among the hospital attending patients could be an underestimation of the actual disease burden in our community, and heightened awareness among the treating physicians about the cardiac diseases could actually reduce the mortality and morbidity associated with these ailments.